A solid-state integrated photo-supercapacitor based on ZnO nanorod arrays decorated with Ag2S quantum dots as photoanode and PEDOT charge storage counter-electrode. - Solis Cortes, Daniel; Navarrete-Astorga, Elena; Sherebler, Ricardo; Peinado-Pérez, Juan José; Martín-Jiménez, Francisco de Paula; Ramos-Barrado, José Ramón; Dalchiele, Enrique A. (Royal Society of Chemistry, 2020)
A planar solid-state photocapacitor with two electrodes has been prepared for the first time using a passivated film of ZnS with Ag2S quantum dots deposited on ZnO nanorods, which were electrochemically grown on ZnO seed layers, as the photoanode. The supercapacitor part is composed of a electrodeposited poly(3,4-ethylene-dioxythiophene) PEDOT film as the counter-electrode and an ionic liquid-based electrolyte between them deposited by the dip coating method. The different nanostructures and electrodes were morphologically and structurally characterized, and the device was electrochemically characterized and could reach a potential of 0.33 V during photocharge and a storage efficiency of 6.83%.
This is an open access article under the CC BY-NC license
Keywords: Energía fotovoltaica - Generación; ZnO; Ag2S; PEDOT; Photo-supercapacitor